Oxidative stress indices and pathological changes in cattle with traumatic pericarditis - HUSSEIN, A. H.; HANAN, K. E.; YASMIN, O. E. (Journal of the Hellenic Veterinary Medical Society, 2018)
Objectives of the study were to provide information on the changes in oxidative stress indices, as well as to describe the possible pathological changes in cattle affected with traumatic pericarditis (TP). Twenty-six cattle with TP were included in the current study. Nine clinically healthy cattle were enrolled as controls. Blood serum samples were collected and stored at -20ºC. Measurement of nitric oxide (NO), malondialdehyde (MDA), total antioxidant capacity (TAC) and other biochemical parameters were done within one week from sampling. Postmortem and histopathological examinations were carried for dead or euthanized cases. The mean values of NO, MDA, creatinine, total bilirubin, globulins, blood urea nitrogen, and total proteins were significantly higher in the diseased group (P<0.05), while the mean values of TAC, glucose and albumin were significantly lowered in TP group (P<0.05). The activities of aspartate aminotransferase (AST) and γ-glutamyl transferase (GGT) were higher in affected cattle than healthy ones. In cattle with TP, a strong significant positive association was found between serum concentrations of NO and MDA. Postmortem examinations of the dead animals revealed severe thickening of the pericardium and accumulation of pericardial effusions either mild or severe in the pericardial sacs. Regarding the recorded histopatholgical changes; Organized fibrinous pericarditis (constrictive pericarditis), necrosis of the myofiber with congestion and hemorrhage in the myocardium, chronic venous congestion of the liver, and hemosiderosis of the spleen were clearly observed. Furthermore, hemorrhage and interstitial fibrosis of the lung, various degrees of degeneration and hyalinization of the renal tubules were prominently featured. In conclusion, oxidative stress and lipid peroxidation may be involved in the complications of traumatic pericarditis in cattle.